1999
DOI: 10.1080/001401399185342
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an EMG-based method for continuous estimates of low back compression during asymmetrical occupational tasks

Abstract: Variables, such as peak and accumulated moments and spine compression forces, have been shown to be risk factors for occupational low back pain. Estimates of these forces during prolonged, dynamic, asymmetric tasks using biomechanical models is complex and time-consuming. A simple technique for continuous measurement of these variables over a prolonged period is needed to measure the distribution of spinal loading during both sagittal plane lifts and complex asymmetrical jobs. The aim of this study was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 9 publications
1
10
1
Order By: Relevance
“…Furthermore, compared to a normal person, his/her postural sway increases in the standing posture [24,25]. His/her medial and lateral postural sway also increase [13]. However, in this study, with eyes closed and open in static balance, the P-COG group's results for static and dynamic COG speed and distance were more decrease than those of the C-COG group (p < 0.05).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, compared to a normal person, his/her postural sway increases in the standing posture [24,25]. His/her medial and lateral postural sway also increase [13]. However, in this study, with eyes closed and open in static balance, the P-COG group's results for static and dynamic COG speed and distance were more decrease than those of the C-COG group (p < 0.05).…”
Section: Discussioncontrasting
confidence: 79%
“…Na et al [12] indicated that trunk muscle weakness was associated with pelvic variables, thereby affecting changes in the lumbar lordosis angle and the lumbosacral angle. On the other hand, according to Mientjes et al [13] the COG was not located posterior to the center in every chronic low back patient. However, Byl and Sinnott [14] indicated that the COG in many chronic low back pain patients was located posterior to the center.…”
Section: Introductionmentioning
confidence: 97%
“…Long-term, mechanical exposure time histories are now being collected via data loggers (e.g. shift long moment or compression normalized EMG, Mientjes et al 1999). The process outlined in this study suggests a potential analysis approach for future epidemiological studies of musculoskeletal disorders where long-duration mechanical exposure data are available (Wells et al 2004).…”
Section: Biological Systems Acting Around Range Of S^5000 Smentioning
confidence: 99%
“…The Biometrics EMG system allows the researcher to collect raw EMG signals within the range of 15e450 Hz, with a common mode rejection ratio (CMRR) at 60 Hz (dB) of more than 96 dB (typically 110 dB), and an input impedance of more than 10 15 Ohms. EMG of the T9 ES has been shown to be a practical method for estimating continuous compression of the spine (Mientjes et al, 1999;Jackson et al, 2008;Potvin et al, 1990). While EMG of the ES was collected at two levels, the T9 and L4/L5, L4/L5 EMG will not be further discussed because it was not as strongly correlated with L4/ L5 moments as the T9 EMG.…”
Section: Emgmentioning
confidence: 97%